The Relationship between physical activity, eating attitudes, and body image dissatisfaction of Romanian students - Barna, Octavian; Popescu, Veronica; Musat , George Cosmin; Georgescu, Adrian; Petcu , Damian (Progress in Nutrition, 2020)
The purpose of this study was to evaluate the relationship between physical activity, eating attitudes, and body image dissatisfaction (BID) of Romanian students. The study was conducted with 934 students aged between 19 and 25 years. A self-administrative questionnaire was used for data collection on social demographic and physical activity and food habits, and a body dissatisfaction scale software assessment tool was used to measure the BID and body image perception (BIP). Anthropometric measurements were used to calculate the body mass index (BMI). A different subgroup of 97 subjects aged between 19 ± 25 years old was randomly selected to participate in an ancillary study, 2 weeks after the initiation of the main study. To determine the strength and direction of linear relationships between pairs of the analyzed data, we calculated Pearson’s correlation coefficient (r) and the associated probability. The level of significance α = 0.05 was used to check the hypothesis. The Kolmogorov–Smirnov test, t-test, and Levene’s test were performed. BID ranged from 0.35 (SD = 0.94) to 1.35 (SD = 0.71) for the male subjects involved in the main study and from 0.74 (SD = 0.64) to 1.82 (SD = 0.78) for the female students. In the main study, the median values of physical activity (PA) ranged from 524.2 (±13.1) to 4,641.8 (±14.3) metabolic equivalent task (MET)·minute/week for male students and from 471.5 (±11.6) to 4,421.4 (±17.9) MET·minute/week for female students. Students who develop a regular practice of high PA and have a healthy diet have a lower BMI and a more favorable body structure and shape. There was a strong association between participation in sports and the BID and BIP. This study showed that BMI is negatively correlated with BID and BIP. There are no significant differences between the BID and BIP means between the main and ancillary studies. The gender differences in BID, BIP, BMI, and weight control practices as PA and diets exist among Romanian students. It is noted that, in the case of female students, there was a sharp increase in BID with the increase in BMI.